Implementation of Family Hope Program (PKH) - jannah, Miftahul; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the implementation of a conditional cash transfer program (CCT) in a rural Indonesian village using Charles O. Jones' model of policy execution. Qualitative data collected through observation, interviews, and documentation revealed the program's strengths and weaknesses. While organizational structures and policy interpretations aligned with central government guidelines, limitations emerged in program application. Key shortcomings included inadequate human resource allocation for participant monitoring, lack of access to necessary facilities, and insufficient community awareness. These findings highlight the importance of context-specific adjustments and improved resource allocation within CCT programs to maximize their impact. Highlight : Organizational structures and policy interpretations: The study found that the program's organizational structures and policy interpretations aligned with central government guidelines. Limitations in program application: Key shortcomings included inadequate human resource allocation for participant monitoring, lack of access to necessary facilities, and insufficient community awareness. Context-specific adjustments and improved resource allocation: The findings highlight the importance of context-specific adjustments and improved resource allocation within CCT programs to maximize their impact. Keywords: Conditional Cash Transfer (CCT), Charles O. Jones' model, policy execution, rural Indonesian village, strengths, weaknesses.